Acute liver failure in neonates, infants and children. (December 2011) - Devictor, Denis; Tissieres, Pierre; Durand, Philippe; Chevret, Laurent; Debray, Dominique
Acute liver failure (ALF) is a rare but devastating syndrome. ALF in children differs from that observed in adults in both the etiologic spectrum and the clinical picture. Specific therapy to promote liver recovery is often not available and the underlying cause of the liver failure is often not determined. Management requires a multidisciplinary approach and should focus on preventing or treating complications and arranging for early referral to a transplant center. Although liver transplantation has increased the chance of survival, children who have ALF still face an increased risk of death, both while on the waiting list and after emergency liver transplantation. This article will review the current knowledge of the epidemiology, pathobiology and treatment of ALF in neonates, infants and children, and discuss some recent controversies.